A three‐dimensional digital microscopic investigation of entheseal changes as skeletal activity markers. Issue 4 (1st May 2019) - Nikita, Efthymia; Xanthopoulou, Panagiota; Bertsatos, Andreas; Chovalopoulou, Maria‐Eleni; Hafez, Iosif
Abstract: Objectives: The current article explores the effectiveness of entheseal changes (EC) as skeletal activity markers by testing the correlation between such changes and cross‐sectional geometric (CSG) properties while controlling for the effect of age and body size. Materials and methods: The originality of the article lies in capturing EC in a continuous quantitative manner using three‐dimensional microscopy. Roughness and bone resorption were recorded on Zones 1 and 2 of three humeral entheses (subscapularis, supraspinatus, and infraspinatus) in a documented sample of 29 male skeletons. Results: Our analysis found that merely 5.91% of the partial correlations between EC and CSG properties were statistically significant. In addition, two unexpected patterns were identified, namely a higher number of significant correlations on the left side entheses compared to the right side ones, and a higher number of correlations between minimum roughness and CSG properties compared to mean and maximum roughness. Discussion: These patterns are the inverse of what we would expect if activity had exerted an important effect on EC expression. Therefore, they support the lack of association between EC and habitual activity, even though various factors potentially affecting the above results are discussed.